THU0445 The Change of Laboratory Markers in Serum Under the Influence of Inhibitor of Interleukin-1 in the Therapy of Secondary Osteoarthritis in Patients with Rheumatoid Arthritis - Starodubtseva, I.; Vasilieva, L.; Nikitin, A.; Barsukova, N. (Annals of the rheumatic diseases, 2015)
BackgroundDiacerein and its active metabolite, rhein, are anthraquinone derivatives. It is considered, that diacerein works by blocking/reducing the actions of interleukin-1β, a protein involved in the process of articular cartilage destruction and synovial inflammation 1-4.ObjectivesTo evaluate the dynamic of COMP, IL-1 in serum and activity on DAS 28 in patients with secondary osteoarthritis in rheumatoid arthritis treated with inhibitor of interleukin-1 and basis therapy.MethodsWe studied 124 patients with secondary osteoarthritis of the knee in rheumatoid arthritis (according to criteria EULAR/ACR) with the mean age of 44.02±9.52 years, the IInd stage of activity on DAS28, and the mean duration of the disease 6.3±4.2 years. Patients were divided into two groups and treated with 10-20 mg of methotrexate each week. Patients of group 1 (n=62) received diacerein 50 mg twice a day on the basis therapy. After the six-month treatment we estimated the dynamic of the level of serum COMP (ELISA), IL-1 (BMS 224/2) and DAS28 across the comparison groups. The model surfaces used for the analysis enabled us to obtain the integral estimation of the indicators' dynamics.ResultsThe constructed model surfaces indicated the decreased levels of IL-1, COMP and DAS28 in group I till 6,68±0,37 pg/ml (p<0,001); 16,92±0,8 ng/ml ×102 (p<0,001) and 2,06±1,19 (p<0,05) respectively. Also the model surfaces revealed the interdependency of all these indicators. The second group reacted to the treatment by decreasing the indicators as well. However, the dynamics of the changes was significantly less. In comparison analysis we noted significant statistical advantages (p<0,01) of the use of diacerein with methotrexate regarding the dynamic of IL-1 and COMP in patients' serum.ConclusionsThe combination of inhibitor of interleukin-1 with methotrexate was more effective in subjects with decreasing levels of IL-1 and COMP in the serum of patients with secondary osteoarthritis in rheumatoid arthritisReferencesYaron M, et al. Anti-interleukin-1 effects of Diacerhein and Rheun in human osteoarthritis synovial tissue and cartilage cultures. Osteoarthritis Cartilage 1999;7(3):272-280.Alvarez-Soria MA, et al. Diacerein has a weak effect on the catabolic pathway of human osteoarthritis synovial fibroblast - comparison to its effects on osteoarthritic chondrocytes. Rheumatology (Oxford) 2008;47(5):627-33.Legendre F, et al. Rhein, the metabolite of diacerhein, reduces the proliferation of osteoarthritic chondrocytes and synoviocytes without inducing apoptosis. Scand J Rheumatol 2009;38(2):104-11.Assessment report for diacerein containing medicinal products. 28 August 2014 European Medical Agency/527347/2014.Disclosure of InterestNone declared